Can biomechanics turn youth sports into a venue for informal STEM engagement?. (February 2023) - Loya, Amy K.; Smith, Phillip E.; Chan, Deva D.; Corr, David T.; Drazan, John F.
Abstract: A common pitfall of existing Science, Technology, Engineering, and Math (STEM) outreach programs is that they preferentially engage youth with a preexisting interest in STEM. Biomechanics has the unique potential to broaden access to STEM enrichment due to its direct applicability to sports and human performance. In this study we examine whether biomechanics within youth sports can be used as a venue for STEM outreach, and whether recruiting participants through youth sports programs could broaden access to the STEM pipeline. We created a four-hour sports science clinic that was performed as part of National Biomechanics Day and invited two groups of student participants: youth recruited through local high school sports programs ("Sports Cohort", N = 80) and youth recruited through existing STEM enrichment programs ("STEM Cohort", N = 31). We evaluated interest in STEM, Sports Science, and Sports using a pre-post survey. Somewhat expectedly, youth recruited through sports programs (Sports Cohort) had a lower baseline interest in STEM and a higher baseline interest in sports, compared to those recruited through STEM programs (STEM Cohort). The Sports Cohort exhibited a statistically significant increase in STEM interest following participation in the clinic, while youth in the STEM Cohort maintained their high baseline of STEM interest. These findings provide evidence that youth sports programs can serve as an attractive partner for biomechanists engaged in STEM outreach, and that situating STEM within sports through biomechanical analysis has potential to introduce STEM interest to a wider audience and to broaden access to the STEM fields among diverse youth.